Comparison of Elastomer Modelling in Various FEM Packages. (2015) - Perduta, Anna; Putanowicz, Roman
Abstract: No one can deny the role of synthetic polymers as engineering materials - they are all around us in our everyday life. Also due to the constant progress in material engineering, polymers, and among them elastomers, find increasing usage in civil engineering. Computer modelling of elastomers requires special description of material and use of non-linear finite element method. Available, free and commercial software use many different approaches in elastomers modelling, thus comparison of results may display discrepancies. Even if used method is the same, its computer implementation may vary, therefore using various software, one can obtain differing output. The paper presents comparison of results obtained from four computational packages devoted to FEA: Abaqus, GetFEM++, Tochnog, FEBio. It can be seen as an overview of the software that can be used in modelling rubber-like components. It highlights differences in material description (for instance in names of hyperelastic laws and employed formulas) and used multi-field variational principles in modelling material's incompressibility. Examples included in the paper can be treated as benchmarks, that can be helpful in verifying third party software or the one developed by readers.